(untitled) (International journal of artificial intelligence, 2025)
This article examines the economic and educational impacts of bilingual education programs in Guatemala, focusing on their costs and benefits. Drawing on quantitative data from primary schools, the study analyzes how bilingual instruction in indigenous languages alongside Spanish influences academic performance, school attendance, repetition, and dropout rates. The findings indicate that bilingual education not only improves learning outcomes in both the native language and Spanish but also reduces grade repetition and dropout rates, generating substantial cost savings for the education system. The paper further explores the broader socio-economic implications of investing in bilingual education, particularly in multilingual and culturally diverse societies.